Theoretical and experimental study of precast reinforced concrete walls with different openings under seismic loads. (1st August 2021) - Dan, D.; Todut, C.; Stoian, V.; Fofiu, M.
Highlights: The use of PRCWP for buildings placed in seismic areas can provide stiffeness, strength and ductility of structures. The cut-out interventions in PRCWP change the seismic behaviour and performance of buildings. The ductility of PRCWP with cut out openings has to be analyzed function of the dimensions and opening ratios. Abstract: The present paper presents the results of an experimental program developed to study the seismic performance of precast reinforced concrete wall panels. The specimens' characteristics and the reinforcement configuration were taken from a typical Romanian project used widely since 1981. The elements were designed at that time without using the principle of shear force associated to the bending resisting moment so they can be therefore considered as large, lightly reinforced walls of medium ductility (DCM). The used specimens were of three situation kinds, namely: as-built blank solid wall, with initial opening and with cut-out opening. The experimental test set-up and the loading strategy were designed to simulate the shear behaviour. Based on the experimental investigations performed on precast RC wall panels, subjected to in-plane reversed cyclic lateral loads, the authors identified the following: the behaviour mode, the critical regions, the maximum lateral load and the displacement capacity at ultimate stage, the cut-out opening influence on the wall's seismic performance and the accuracy of theoretical estimations.